An introduction to assessing development projects of the Al-Ghab Plain in according to the spatial development concepts of the emerging rural communities (Journal of Hama University, 2021)
Emiratization projects are one of the basic entrances to comprehensive spatial development, and one of the main solutions for distributing the population in a balanced way. They guarantee a change in social and economic conditions with the aim of developing human and economic resources and raising their social level, and they are carried out in different patterns and the agricultural pattern is considered one of the most important.The attraction of the Al-Ghab region to development projects since the mid-twentieth century, represented by the drying and reclamation project of the Al-Ghab Plain and until now clearly through the development project of Agropolis, has resulted in the emergence and development of separate population centers in the countryside of this plain, and along it and large proportions of the lands reclaimed from it, as well as high rates of Population growth in the administrative jungle region, as the overall population growth rates for Syria exceeded the time period between 1970-1981.This research aims to study the multiple approaches to achieving the spatial development of the emerging rural population centers and using them in evaluating the development projects of the Al-Ghab Plain, based on the analysis of a number of relevant Arab and international experiences, and identifying different methods to achieve integration in its spatial planning